2020
DOI: 10.1097/bsd.0000000000000996
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Bupivacaine Is Both Safe and Effective in Controlling Postoperative Pain After Spinal Surgery in Children

Abstract: Study Design: Retrospective comparative cohort study. Objective: To evaluate: (1) pain relief efficacy; (2) opioid consumption; (3) length of stay (LOS); (4) discharge disposition (DD); and (5) safety and adverse effects of liposomal bupivacaine (LB) in pediatric patients who underwent spinal deformity correction. Summary of Background Data: LB is a long-acting, locally injectable anesthetic. Previous orthop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…In the current study, patients who received LB experienced shorter in-hospital LOS than those who received non-LB analgesia. This finding is consistent with previous reports in adult 22,23 and pediatric 17 patients undergoing spine surgery, as well as studies in adult patients in other surgical areas. 24,25 Use of opioids in the postanesthesia care unit may contribute to ORAEs, possibly resulting in an increase in LOS and total costs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the current study, patients who received LB experienced shorter in-hospital LOS than those who received non-LB analgesia. This finding is consistent with previous reports in adult 22,23 and pediatric 17 patients undergoing spine surgery, as well as studies in adult patients in other surgical areas. 24,25 Use of opioids in the postanesthesia care unit may contribute to ORAEs, possibly resulting in an increase in LOS and total costs.…”
Section: Discussionsupporting
confidence: 93%
“…These clinical and economic benefits are in accordance with and expand upon results from other retrospective studies examining the use of opioid consumption and LOS for pediatric patients receiving LB or non-LB analgesia for postsurgical pain after spine deformity surgery and LOS for adult Medicare patients undergoing total knee arthroplasty. 17,18 Adolescents (defined by the World Health Organization as those aged 10-19 years) 19 may be at increased risk of opioid misuse compared with adults. This may be explained by changes in brain reward and habit formation centers during this developmental period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both retrospective studies investigated the use of LB as an adjunct to existing multimodal pain regimens in patients undergoing pediatric spinal deformity correction. 33,34 Cloyd et al found no difference in postoperative opioid use or postoperative pain scores with use of LB in their study. On the other hand, Chughtai et al found that the addition of periincisional LB at closure of surgery improved these aforementioned metrics.…”
Section: Discussionmentioning
confidence: 67%
“…They also failed to reduce the total dose of opiate medications, shortening only the duration of the required administration [25]. In contrast, liposomal bupivacaine, injected into paraspinal musculature, demonstrated a reduced pain score in paediatric patients subjected to spinal surgery [26].…”
Section: Discussionmentioning
confidence: 99%